Examining the performance oriented indicators for implementing green management practices in the Indian agro sector. (1st April 2019) - Raut, Rakesh D.; Luthra, Sunil; Narkhede, Balkrishna E.; Mangla, Sachin K.; Gardas, Bhaskar B.; Priyadarshinee, Pragati
Abstract: Green management is a strategic approach to minimize an organizational supply chain effect on the environment while expanding its economic performance. In so doing, performance focused dimensions are imperative in optimizing resources consumption and accomplishing sustainability concepts in an organizational context. In the present study, 'hard (operational and technology-based) and soft (human resource based)' performance indicators of the green value chain are analyzed in the Indian agro-based industry context. The performance indicators were identified using literature resource and further analyzed by using a quantitative approach. Several hypotheses were formulated for exploring the interrelationship between the 'green practices' and 'business performance' in the agro sector. For this work, 490 responses were gathered from a diverse set of respondents. Research findings reveal that 'Collaborative Green Transportation and Cold storages' have a higher influence on operational performance. The present research can assist managers, regulating authorities, and decision makers in understanding the linkage between the green-focused - operational and human resource related factors and business operational performance in agro food supply context. Based on the findings, the decision makers need to develop policies for improving the overall efficiency of the case sector. Researchers can carry out investigations by applying various multi-attribute decision making tools and formulating hypothesis, which can be further tested by statistical tools across various industries and in different economies. Graphical abstract: Image 1 Highlights: Explored 'Hard and Soft' indicators for evaluating green management practices. Empirically evaluated the green management practices in Indian agro industry. Explored interrelationship between the 'green practices' and 'business performance'. 'Collaborative Green Transportation and Cold storages' is a significant outcome. Provided theoretical & practical implications for improving operational performance.